Modeling for the analysis of the investment potential of the construction sector - Shlafman, Natalya (Array, 2018)
The purpose of the article is to develop a methodology for determining the need for the amount of investment resources needed to build the investment potential (IP) of the construction sector. The methodology is found in economic and mathematical modelling. We developed a model for the analysis of the investment potential of the construction sector (IPCS) by selecting the three-factor Cobb-Douglas production function for the IPCS study and by constructing a functional dependence from the collected statistical information, which allowed us to analyse the effect of changing the value of one of the selected factors on the resulting factor. The paper shows that market participants can use the proposed methodology to determine the factors that influence the improvement of IPCS, the degree of their influence and the determination of the values necessary to achieve a given level of investment potential.